2015
DOI: 10.1007/s00289-015-1386-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical properties of polyvinyl alcohol composite films containing copper oxide nanoparticles as filler

Abstract: This study has been conducted to investigate the effect of incorporating CuO nanoparticles inside PVA matrix with the aim of enhancing the mechanical properties of PVA for reinforcement purposes. Films were prepared by solution intercalation technique with 0.5, 1.0, 1.5 and 2.0 wt% CuO nanofiller content taking neat PVA as the reference for the study. Structural characterisations of the prepared nanocomposite films were carried out by FTIR, SEM and XRD techniques. Various mechanical parameters such as tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Composite materials consisting of metal nanoparticles embedded in a transparent host matrix have attracted the attention of researchers recently as advanced technological materials such as solar cells for photoelectric conversion, transistors for electronic switches [1][2][3][4][5] because of their unique optical, electronic [6], mechanical [7] and structural [8] properties. Large interfacial area between the matrix and nanofiller is a key field of interest in nanocomposites since the nanomaterials possess high aspect ratio and large surface area [9].…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials consisting of metal nanoparticles embedded in a transparent host matrix have attracted the attention of researchers recently as advanced technological materials such as solar cells for photoelectric conversion, transistors for electronic switches [1][2][3][4][5] because of their unique optical, electronic [6], mechanical [7] and structural [8] properties. Large interfacial area between the matrix and nanofiller is a key field of interest in nanocomposites since the nanomaterials possess high aspect ratio and large surface area [9].…”
Section: Introductionmentioning
confidence: 99%
“…Film toughness for ZTA in PVA matrix was calculated by the area under the curve of Tensile Stress v/s Tensile Strain graph [17,18,20]. Figure 11 shows the effect of ZTA loading on film toughness.…”
Section: Effect Of Zta Loading On Film Toughnessmentioning
confidence: 99%
“…Polyvinyl alcohol (PVA) is a most preferred material of choice as a host matrix by various researchers [17][18][19][20][21][22] for the synthesis of polymer nanocomposites due its water soluble, non-toxic, ease of fabrication, transparent film forming ability, biodegradability, chemical stability and interesting mechanical properties. PVA is a semi-crystalline polymer with high optical clarity [20].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, nanozinc oxide, nanotitanium dioxide, nanomagnesium oxide, and other nanosized metal oxides of the main element of the second cycle and the third cycle of the subgroup elements have a wider application range and greater influence. [19][20][21][22] Rao et al 23 found that the mechanical properties of polyvinyl alcohol composite film with copper oxide nanoparticles as filler were enhanced.…”
Section: Introductionmentioning
confidence: 99%